(untitled) (Bangladesh Journal of Botany, 2026)
This study investigates the phytochemical composition, antioxidant potential, and chemical profile of cumin seeds (Cuminum cyminum) using phytochemicals (polyphenols, flavonoids and tannins) screening, DPPH antioxidant assay, and Gas Chromatography–Mass Spectrometry (GC–MS) analysis. Results revealed significant levels of polyphenols (36.42%), flavonoids (32.86%), and tannins (17.41%) in the ethanolic extract, which also showed the highest extraction yield (10.61%) compared to the aqueous extract. Antioxidant activity, assessed via DPPH assay, showed stronger radical scavenging in ethanolic extract (IC₅₀ = 101.95 µg/ml) than water extract (IC₅₀ = 147.55 µg/ml). GC-MS analysis identified various fifty bioactive compounds in the extracts. These findings highlight cumin seeds as a rich source of phenolics with notable antioxidant properties, supporting their potential use in functional foods and natural therapeutics. Bangladesh J. Bot. 55(1): 101-106, 2026 (March)